MACROECONOMIC IMPACTS OF THE INTEREST RATE SHOCKS IN THE SELECTED EURO AREA COUNTRIES - ĎURČOVÁ, Júlia (Journal of Advanced Studies in Finance, 2012)
The following paper aims at analysing the impact of a shock in interest rate on selected economic variables in the five European Union member countries (Germany, France, Netherlands, Belgium and Luxembourg). The analysis shall be done through the VAR method where we will use the approach of the recursive Cholesky decomposition of the variance-covariance matrix. We expect that the results of the analysis will enable us to determine the shock impact on the development of the selected variables. The data necessary for the analysis will be taken from the IMF, BIS, Eurostat and ECB statistics collected in the time period 2002 - 2012.